Perancangan Fasad dan Interior Pusat Pelatihan Pijat Difabel berbasis budaya lokal di Pusat Pelayanan Griya Harapan Difabel Kota Cimahi - Togar Mulya Raja; Erlana Adli Wismoyo; Mohd Ridho Kurniawan (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The Griya Harapan Difabel Social Service Center (Pusyansos GHD) offers guidance programs for people with disabilities, encompassing physical, mental, social, and spiritual aspects. One of the successful outcomes is the production of batik, which has gained wide recognition and contributed to the growth of local SMEs. This community service project focuses on providing comfortable facilities for massage skills training for people with disabilities. Currently, the training space needs a redesign to enhance comfort and safety for its users. The proposed solution involves a disability-friendly design with unique aesthetic features. It is expected that this improved training facility will enhance massage skills, create new business opportunities, and provide a sustainable income source for the community.